2018
DOI: 10.18203/2394-6040.ijcmph20180745
|View full text |Cite
|
Sign up to set email alerts
|

The effect of female genital mutilation on couple sexual function

Abstract: Background: Female genital mutilation (FGM) is a procedure that had physical, social, psychological, and sexual complications. The study aimed to assess effect of FGM on couple sexual function.Methods: case control nested from cross-sectional study in Fayoum governorate; it was conducted during a period of five months (March 2016 to July 2016).Results: The prevalence of FGM was 432(83.4%). The risk of exposure to mutilation was about four folds higher among women inhabitant rural areas, and about nine folds hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Healthcare utilisation associated with FGM was based on a review and meta-analysis of the literature on clinical complications associated with FGM 19–109. All complications for which a significant association with FGM was found, and for which corresponding interventions could be identified, were included in the healthcare utilisation calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Healthcare utilisation associated with FGM was based on a review and meta-analysis of the literature on clinical complications associated with FGM 19–109. All complications for which a significant association with FGM was found, and for which corresponding interventions could be identified, were included in the healthcare utilisation calculations.…”
Section: Methodsmentioning
confidence: 99%
“…In study of Raheem et al, the mutilated women’s husbands had impotence and premature ejaculation for twice more, and less sexual satisfaction was seen in 56%. There was a significant relationship between women mutilation and existence of psychological and social marriage problems ( 24 ). Peltzer and Pengpid found out that the mutilated women experience the sexual partner’s violence two times more than others ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies on the sexual consequences of FGM in Iran is mostly related to sexual function ( 3 , 4 , 23 ), while sexual quality of life is a more objective criterion for studying the effects of FGM on women’s sex life. On the other hand, some researchers have reported that there is a significant relationship between women mutilation and psychological and social marriage problems ( 24 ). This study aimed to compare the sexual quality of life, as well as marital relationship, in the mutilated women with other women living in Kurd region of Mahabad (Iran).…”
Section: Introductionmentioning
confidence: 99%